Congenital absence of norepinephrine due to CYB561 mutations. (14th January 2020) - Shibao, Cyndya A.; Garland, Emily M.; Black, Bonnie K.; Mathias, Christopher J.; Grant, Maria B.; Root, Allen W.; Robertson, David; Biaggioni, Italo
Abstract : Objective: Cytochrome b561 (CYB561) generates ascorbic acid, a cofactor in the enzymatic conversion of dopamine to norepinephrine by dopamine β-hydroxylase. We propose that the clinical relevance of this pathway can be revealed by characterizing the autonomic and biochemical characteristics of patients with CYB561 mutations. Methods: We performed autonomic evaluations in 4 patients with lifelong orthostatic hypotension in whom CYB561 mutations were determined by genomic sequencing. Results: Patients had disabling lifelong orthostatic hypotension (OH) and impaired blood pressure response to the Valsalva maneuver (VM), with exaggerated hypotension during phase 2 and lack of overshoot during phase 4. Heart rate ratios for sinus arrhythmia and the VM were normal. Plasma norepinephrine and metabolites were undetectable, and plasma dopamine and metabolites were normal. Droxidopa restored norepinephrine levels and improved OH. Patients 1 and 2 were sisters and homozygous for a nonsense mutation in exon 2, c.131G>A, p.Trp44 (Circ Res 2018). Their brother (patient 3) died at age 16 and his DNA was not available. Patient 4 was compound heterozygous; one allele had a missense mutation in exon 2, c157C>T, p.His.53Tyr, and the other had an exon 2 deletion. Conclusion: CYB561 deficiency is characterized by selective sympathetic noradrenergic failure with lifelong, disabling OH but with normal sympathetic cholinergic (sweating) and parasympathetic (heart rate regulation) functions. We report a novel case of CYB561 deficiency due to an exon 2 deletion in one allele and a missense mutation in the other. These patients highlight the critical role CYB561 plays in sympathetic function and cardiovascular regulation.